Exploring the link between HRPractices, Employee Motivation, Employee Empowerment and Employee Performance in Engineering Firms of Indonesia - Saengchai, Sakapas; Siriattakul, Parinya; Jermsittiparser, Kittisak (International Journal of Psychosocial Rehabilitation, 2019)
The prime aim of this research is to examine the link between HR practices, employee motivation, employee empowerment and employee performance in Engineering firms of Indonesia. The mediating role of employee motivation and moderating employee empowerment is also examined. The study has employed the surveybased methodology to accomplish the objectives of research and to answer research questions. The tool used for data analysis in current study isSEM-PLS. The data collection is done from employees of engineering firms in Indonesia. Stratified random sampling is used for sampling of data. The findings of the study have shown agreement with the proposed findings and have argued the HR practices, employee motivation, and employee empowerment as the determinants of employee performance of employees working in the Engineering firms of Indonesia. Current study is among the pioneering study on the issue and will help the researchers and academicians in understanding the issue related to employee performance among the employees in Engineering firms of Indonesia.